Xylem vessel radii comparison between soybean genotypes differing in tolerance to drought. Issue 3 (3rd May 2020) - Nogueira, Marco; Livingston, David; Tuong, Tan; Sinclair, Thomas R.
ABSTRACT: Xylem element radius can be a key factor in determining plant hydraulic conductance and vulnerability to cavitation. Most studies of xylem element radius have been on woody species with a focus on plant survival under severe water-deficit stress. However, xylem element radius, particularly the largest radius elements, can potentially have an influence on hydraulic flow at more moderate water-deficits. Few studies have offered a detailed distribution of xylem element radii, and even fewer on the distribution in crop species. In this study, the xylem element radii of two genotypes of soybean ( Glycine max L. Merr.) were compared because these two genotypes had been documented to react differently to drying soil. The stems of young plants were harvested from three positions, and in stem cross-sections, the number of xylem elements and the radius of each element were determined. While the number of xylem elements did not differ significantly between the two genotypes, the distribution of the radii was skewed to smaller radii in drought-tolerant PI 4719386 as compared to Hutcheson. This contrast extended to a difference between the genotypes in the radii of the largest elements, which are considered most vulnerable to cavitation.